High-intensity interval training in Diabetes Mellitus: A short systematic review - Nieczyporuk, Mateusz; Sikora, Aleksandra; Skweres, Martyna; Pucyło, Szymon; Ceglarz, Katarzyna; Pielaciński, Jan; Rudnik, Aleksander; Sikora, Kinga; Piotrowska, Gabriela (Journal of Education, Health and Sport, 2025)
In recent decades, diabetes has become a prominent health concern in the developed world, with numerous researchers suggesting that it should be designated as the pandemic of the 21st century. Both type 1 and type 2 diabetes are on the rise, yet the latter poses a particularly significant threat. It is important to note that in a substantial number of cases, the underlying risk factors for type 2 diabetes are amenable to modification, highlighting the potential for preventative strategies. A major contributing factor is low physical activity, which significantly impedes disease control once it has developed.HIIT has been identified as a potentially effective and time-saving physical activity alternative for people with and at risk of diabetes. A comprehensive analysis of 12 papers from the 513 papers in the PubMed database was conducted, highlighting the substantial benefits of HIIT, including the immediate reduction in glucose levels post-training and the enhancement of the daily glycaemic profile due to increased insulin sensitivity of tissues. Similar observations were made regarding the reduction in systolic blood pressure and pro-inflammatory cytokines.